2019
DOI: 10.1024/1421-0185/a000225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Type of Childcare on Toddlers’ Motor, Social, Cognitive, and Language Skills

Abstract: Abstract. This study investigated the relationship between type of childcare and toddlers’ skills in four important developmental domains: motor, cognitive, social, and language. A total of 637 children aged 18 and 24 months were either cared for exclusively at home by their parents or relatives ( home-care group) or attended a daycare center for a minimum of 2 days per week ( center-care group). We tested the children’s skills using standard assessment tools and compared the skills of the two care groups. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…A fourth study focused on motor, cognitive, language, and social skills but did not measure problem behavior. Toddlers who attended a daycare center for at least two days a week did not differ from children cared for by family members on the measured domains [ 60 ]. All four studies (based on regression models) included only few control variables and a sample of relatively advantaged families.…”
Section: Introductionmentioning
confidence: 99%
“…A fourth study focused on motor, cognitive, language, and social skills but did not measure problem behavior. Toddlers who attended a daycare center for at least two days a week did not differ from children cared for by family members on the measured domains [ 60 ]. All four studies (based on regression models) included only few control variables and a sample of relatively advantaged families.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies found discrepant results in this regard because children who attended daycare are generally considered more socially competent, but it is not so clear whether they are also more prosocial than those who did not attend it (Erel et al, 2000;Belsky et al, 2007;Ansari, 2018;Bleiker et al, 2019). At the same time, daycare attendees may also be more involved in and exposed to aggressive behaviors among peers, as children exhibit their peak of physical aggression generally between 18 and 30 months of age (Huston et al, 2015;Pingault et al, 2015;Filho et al, 2016;Ansari, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…In this regard, available evidence testifies that the daycare experience can either positively or negatively influence child development, or not influence it at all, as shown by various studies concerning cognitive and communicative-linguistic development (Bulgarelli and Molina, 2016;Bleiker et al, 2019). With specific reference to social-emotional and behavioral skills, the main hypothesis is that early relational experience with an extended peer group can foster general capacities for understanding other children and their needs and, consequently, promote prosocial behavior.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In particular, findings mostly reported that children who attend center-based care seem to score higher in cognitive tasks compared to their peers in family home-based care [37,38]. On the other hand, results from studies considering potential associations and differences in children's socioemotional development in a different type of care settings appear still ill-defined, suggesting a need for further evaluations and considerations [39][40][41].…”
Section: Participant Characteristicsmentioning
confidence: 99%